2021
DOI: 10.1097/opx.0000000000001837
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Significant Hyperopia in Preschool Children Using Two Automated Vision Screeners

Abstract: Moderate to high uncorrected hyperopia in preschool children is associated with amblyopia, strabismus, reduced visual function, and reduced literacy. Detecting significant hyperopia during screening is important to allow children to be followed for development of amblyopia or strabismus and implementation of any needed ophthalmic or educational interventions.PURPOSE: This study aimed to compare the sensitivity and specificity of two automated screening devices to identify preschool children with moderate to hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Additional analysis showed that as the magnitude of hyperopia (on cycloplegic refraction) increased over the range of 4 D to 10 D, the sphere power measurement of the Power Refractor did not increase correspondingly, suggesting the potential for photoscreeners to fail to identify significant hyperopia. 32,42 Lea Symbols visual acuity testing at 10-feet viewing distance had somewhat higher sensitivity than HOTV visual acuity testing for identification of 1 or more vision disorders, but the differences were not statistically significant. 19 Referral criteria have been published previously for noncycloplegic retinoscopy, Retinomax and SureSight autorefractors, Lea and HOTV visual acuity tests, Power Refractor II, and Random Dot E and Stereo Smile II stereoacuity (tests that did not use a central reading center for test interpretation).…”
mentioning
confidence: 75%
“…Additional analysis showed that as the magnitude of hyperopia (on cycloplegic refraction) increased over the range of 4 D to 10 D, the sphere power measurement of the Power Refractor did not increase correspondingly, suggesting the potential for photoscreeners to fail to identify significant hyperopia. 32,42 Lea Symbols visual acuity testing at 10-feet viewing distance had somewhat higher sensitivity than HOTV visual acuity testing for identification of 1 or more vision disorders, but the differences were not statistically significant. 19 Referral criteria have been published previously for noncycloplegic retinoscopy, Retinomax and SureSight autorefractors, Lea and HOTV visual acuity tests, Power Refractor II, and Random Dot E and Stereo Smile II stereoacuity (tests that did not use a central reading center for test interpretation).…”
mentioning
confidence: 75%
“…The PowerRefractor was previously found to be less precise in measuring refractive error for individuals with high hyperopia, 36 and the PowerRef II showed less accuracy in detecting significant hyperopia. 53 This difference could have resulted from individuals accommodating through their hyperopia during measurements because they were not cyclopleged, making the use of the PowerRef 3 and its predecessors potentially less accurate as a screening tool for detecting hyperopic refractive error. Participants in the current study were required to have a (corrected) visual acuity of 0.1 logMAR (20/25 Snellen equivalent), but refractive error was not obtained, and future investigations should examine the influence of refractive error on agreement.…”
Section: Discussionmentioning
confidence: 99%
“…In practice, commercial photorefractors obtain images of both eyes simultaneously to estimate their refractive state. [3][4][5] To do this, the field of view of the infrared camera is expanded, thus compromising the spatial resolution of each eye's image representation. Should the proposed technology translate into commercial use for identification of eyes with corneal distortions, it should be able to produce results like Figs.…”
Section: Impact Of Image Resolution On the Photorefraction Luminance ...mentioning
confidence: 99%
“…Commercially available photorefractors (e.g., Spot Vision Screener, Welch Allyn and Plusoptix S16, Plusoptix GmbH) meet all these criteria for screening refractive anomalies of the eye. [3][4][5] They are noninvasive with a measuring distance of 1 m, handheld, and able to obtain synchronous data from both eyes rapidly (measurements require no more than a few seconds) and can be operated by nontechnical staff with minimal training. These devices are also quite tolerant to head movement and thus do not require precise control of head position.…”
Section: Hypothesis 2: Differentiating Distorted Corneas From Control...mentioning
confidence: 99%
See 1 more Smart Citation